The Theatre of the Oppressed as a method for the praxis of Social Community Psychology and Popular Education in the rural environment - Thelma Maria Grisi Velôso; Marcos Pablo Martins Almeida; Arthur Marcell Campos Arruda; Lisa Martha Silva David; Mateus Rafael Uchôa Dantas; Sarah Lavínia Pereira de Morais (Universidade Federal do Norte do Tocantins, 2021)
This goal of this article is to reflect on the contributions of the method of the Theatre of the Oppressed used by a university extension experiment at a rural settlement in the city of Campina Grande (Paraíba/Brazil). This experiment was based both on Social Community Psychology and on Popular Education addressed to physical education and affectivity, envisaging stimulating and strengthening listening opportunities and the problematization of reality, supporting the autonomy and social leadership. The psycho-pedagogical workshops carried out with a group of children and a group of adolescents was one of the methodological instruments used. The workshops intended to stimulate the taste for reading, creativity, and the critical reflection and autonomy by using reading and social strategies, recreational games and different artistic languages, such as the method of the Theatre of the Oppressed. This method was also used through the presentation of a play for the community, which was assembled according to the forum-theatre technique based on information obtained in the settlement. Starting from the report after three workshops and after the forum-theatre experiment they concluded that the method of the Theatre of the Oppressed aligns to the theoretical perspectives adopted and contributes to the development of more participative, critical and solidarity postures envisaging social changes.